A 15 month - old Bangladeshi Baby With Very Severe Hypertriglyceridemia, Secondary to Glycogen Storage Disease (KYAMC Journal, 2021)
Hypertriglyceridemia is increasingly identified in children and adolescents, due to improved screening and higher prevalence of childhood obesity. The etiologic origin can be primary (genetic) or secondary, but it is often multifactorial. Management is challenging because of the interplay of genetic and secondary causes and lack of evidence-based guidelines. In this case report a fifteen month old boy was incidentally found with hypertriglyceridemia while finding the cause of his abdominal distension and was managed with oral and intravenous medications.KYAMC Journal. 2021;12(3): 182-186